The influence of phase purity on the stability of Pt/LaAlO3 catalysts in the aqueous phase reforming of glycerol. (December 2022) - Inns, D.R.; Pei, X.; Zhou, Z.; Irving, D.J.M.; Kondrat, S.A.
Abstract: Aqueous phase reforming (APR) of waste oxygenates offers the potential for sustainable hydrogen production. However, catalyst stability remains elusive, due to the aggressive hydrothermal conditions employed. Herein, we show that the catalytic performance and stability of Pt supported on LaAlO3 catalysts for glycerol APR is strongly influenced by the phase purity of LaAlO3 . Calcination of the support at 700 °C produces the LaAlO3 perovskite phase and an amorphous lanthanum carbonate phase, which can be removed by calcination at higher temperature. Catalysts comprised of phase pure LaAlO3 were notably more active, with a support calcination temperature of 1100 °C resulting in 20.4% glycerol conversion (TOF 686 h −1 ) in a 2 h batch reaction. Interestingly, all the catalysts, regardless of LaAlO3 phase purity, eventually transform into Pt/LaCO3 OH-AlO(OH) during reaction, but only in the presence of evolved carbon dioxide, itself produced from glycerol reforming. Studies using simulated reaction products showed that organic acid products (lactic acid), in the absence of CO2, facilitated La leaching and loss of crystallinity. A carbonate source (CO2 ) is essential to limit La leaching and form stable Pt/LaCO3 OH. Pt supported on LaCO3 OH and AlO(OH) are stable and active catalysts during APR reactions. Yet, the rate of perovskite phase decomposition strongly influences the final catalyst performance, with the initially phase impure LaAlO3 decomposing too quickly to facilitate Pt redistribution. LaAlO3 calcined at higher temperatures evolved more slowly and consequently produced more active catalysts. Highlights: Pt/LaAlO3 phase transforms into stable Pt/LaCO3 OH-AlO(OH) under APR. Initial perovskite phase purity is key for activity in the APR of glycerol. Rate of catalyst restructuring is affected by initial phase purity of perovskite. Organic acidic products (lactic acid) facilitate La leaching from perovskite. Production of CO2 forces formation of LaCO3 OH limiting La leaching.